Sliding mode observation of capacitor voltage in multilevel power converters - Almaleki, Masoud (2011)
Smart power supply grids may be required to link future energy production and consumers. Multilevel converters are a building block for smart grids. There are several structures of multilevel converters, for example the Neutral Point Clamped (NPC), the Flying Capacitor Circuit and the Cascaded H-Bridge (CHB) converter. The modular structure of the CHB multilevel converter makes it one of the best options for smart grids. Using modular converter structures reduces production and maintenance costs.